The collection of Reuleaux models of the Faculdade de Engenharia da Universidade do Porto - João Manuel Ribeiro da Silva Tavares (2006)
The Faculdade de Engenharia da Universidade do Porto (FEUP) owns a major collection of Reuleaux kinematical models. The history of the purchase of this collection by the Academia Polytechnica of Porto (the predecessor of FEUP) in the late XIX century, and its early use in Porto is well documented and has been the object of several recent papers, circulated predominantly in Portugal. The size - more than one hundred models - and the perfect state of conservation of the collection justify making the international community of experts in the history of machines and mechanisms aware of this heritage. The communication will be arranged in two separate sections. Firstly, a brief reference to the components of the collection will be made. The man behind that purchase, Joaquim de Azevedo Albuquerque, creator of the Gabinete de Cinemática da Academia Polytechnica (Kinematical Unit at the Polytechnical Academy) , will be evoked. The circumstances of the purchase and the initial use of the collection in the teaching of Mechanics and in the dissemination of science will be mentioned. Secondly, some examples of the use of the collection nowadays will be given, including - further to the basic visual use of some models as support of relevant concepts - the 3D computational modeling and virtual animation of several complex collection items by third year Mechanical Engineering and fourth year Management and Industrial Engineering degree students of FEUP.